Nanomedicine-based drug delivery strategies for the treatment of atherosclerosis - Yongfang Lin; Ruibo Lin; Han-Bin Lin; Shiyang Shen (Elsevier, 2024)
Atherosclerosis, a highly prevalent cardiovascular disease, has significantly contributed to morbidity and mortality worldwide. Despite the availability of various treatment options in clinical practice, complete reversal of the atherosclerotic pathological process remains challenging. Traditional anti-arteriosclerosis drugs often suffer from poor solubility, limited targeting ability and obvious adverse effects. Additionally, novel therapeutics such as genetic and protein-based drugs inherently suffer from instability issues, thereby compromising their actual curative efficacy and impeding further clinical application. Recently, nanomedicine-based drug delivery strategies have emerged as promising approaches for treating atherosclerosis due to their ability to specifically transport various drugs to target cells, microstructures and specific molecules within lesion sites. These advanced features enhance drug properties and bioavailability while minimizing off-target effects. Moreover, numerous studies have demonstrated that nanomedicine not only inhibits plaque progression but also reduces lesional areas and eventually reverses atherosclerosis. The utilization of nanomedicine is considered an important therapeutic tactic for further mitigating residual risks associated with atherosclerosis. This review provides a comprehensive overview of emerging nanomedicine-based strategies for targeted delivery of anti-atherosclerosis drugs, elucidating their distinct mechanisms and highlighting their remarkable efficacy in combating atherosclerosis. Additionally, critical challenges and future perspectives associated with the development and application of anti-arteriosclerosis nanomedicine are thoroughly discussed.